Factors influencing performance of village health posts in Kalasin Province, Thailand - Suwannachat, Bunpode; Chompikul, Jiraporn; Mongkolchati, Aroonsri; Keiwkarnka, Boonyong (Journal of Public Health and Development, 2019)
A descriptive study was conducted to identify factors influencing performance of village health posts (VHPs) at Kalasin province, Thailand. Ninety-two VHPs responded the questionnaires during 15 June 2012 to 15 December 2012. The response rate was 74.2 %. Chi-square test and multiple logistic regression were used to examine the association between independent variables and performance of VHPs. Thirty- five VHPs (38 %) were categorized to high performance and 57 VHPs (62 %) to low performance according to cut off point of mean activities (3.58 visits per day) done by each VHP. Community health group, community health fund, distance from a VHP to a health center more than 3 kilometers, financial support for village health volunteer and participation of community leader in VHP execution were found significant association with performance of VHPs (p-value < 0.05). Multiple logistic regression revealing significant predictors for performance of VHP composed of financial support for village health volunteers and participation of community leaders in VHP execution. When controlling other factors, VHPs with financial support for health volunteers were 5.9 times more likely to have high performance than those with no financial support. VHPs with high level of community leader participation in execution of VHPs was 10.1 times more likely to have high performance than those with low participation groups. The finding of this study suggested that providing of financial support for village health volunteers and promotion of community leader participation in VHP execution can boost performance of VHPs.